Peningkatan Kreativitas Siswa dalam Pembelajaran PPKn melalui Metode Problem Based Learning (PBL) - Nahar, Thohirotun; Hanifah, Afnan Nur; Anam, Khairul; Hanik, Elya Umi (Lembaga Yasin AlSys, 2022)
This study aims to increase the creativity of third grade students of MI Miftahul Huda in the first semester of the 2021 academic year in the subject of PPKn Theme 3 Sub-theme 4 (KD 3.4 and 4.4)